Penggunaan Huruf Miring dan Kapital dalam Novel “Hati Suhita” Karya Khilma Anis - Amirullah , Muhammad Amin; Nadila Devi Tsabita; Rahmawati, Fadilah; Afrizal, Mohammad (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
This study aims to analyze the use of italics and capital letters in the novel Hati Suhita by Khilma Anis based on the General Guidelines for Indonesian Spelling (PUEBI). This study uses a qualitative descriptive approach with text analysis techniques on quotations in the novel that contain italics and capital letters. The results of the study indicate that there are various forms of inconsistencies in the use of italics, especially in words in regional languages ​​(Javanese), foreign terms, and non-standard words that are not italicized as they should be. Meanwhile, errors in the use of capital letters were found in the form of inappropriate capitalization of common nouns, greetings, and after punctuation that does not start a new sentence. Of the total data analyzed, more than half of the quotations showed deviations from applicable spelling rules. These errors have an impact on the clarity of meaning, stylistic nuances, and readers' perceptions of the narrative structure. This study emphasizes the importance of spelling accuracy in literary works, not only as a technical aspect, but also as part of the rhetorical and aesthetic power of the text. These findings are expected to be a reference in editing literary works and teaching Indonesian based on spelling.